When robots inherit the Earth: A hiperstitional hypothesis around the Fourth Industrial Revolution founded on the past and present of physical–digital convergence (ARQUISUR Revista, 2022)
This article proposes an archeology of facts that build the integration of the machinic with the human, the productive with the social, and the fictional with the techno-political, at the same time that it describes some lines of thought that, concatenated, point towards a scenario of evolution of the integration between human action and artificial intelligence, as the epitome of machinic evolution in the Fourth Industrial Revolution.
Keywords: Fourth Industrial Revolution; Anthropocene; Machine; Convergence; Artificial Intelligence; Robots